Analisis Kualitas Vigin Coconut Oil (VCO) Produksi Tiga Kelapa di Kabupaten Minahasa Utara. - Sumayku, Bertje R. A.; Tanor, Meity N (EUGENIA, 2018)
This study aims to analyze the quality of virgin coconut oil (VCO) produced by Tiga Kelepa in North Minahasa Regency. VCO made from fresh coconut is one of the essential oils that are widely used for health. This research was conducted from March until May 2018. This research used a description method from the product of the VCO manufacture by stimulating method then continued with quality analysis in the laboratory of PT. Sucofindo and compared with the Indonesian National Standard (SNI) VCO quality. The results showed that the quality of "Vigin Coconut Oil (VCO)" "Tiga Kelapa" production in North Minahasa is better than the quality of Indonesian National Standards. The content of free fatty acids (FFA), water content, iodine number, color and aroma are suitable with SNI VCO. The composition of VCO fatty acids is dominated by Kaprilic Acid, Capric Acid, and Lauric Acid which are higher in content than SNI VCO. Lauric acid acid gives an analysis value of 57.78% Keywords: Three Coconut Production, Quality, Virgin coconut oil (VCO)